Biological hydrogenated carbon-iron composite material, preparation method and application

The preparation of biohydrogenated carbon-iron composite materials through hydrothermal method solves the problems of easy corrosion and inactivation of materials in the prior art, and achieves efficient adsorption and reduction of trichloroethylene in groundwater. It has dual advantages and is suitable for deep repair of groundwater containing trichloroethylene.

CN119771348APending Publication Date: 2025-04-08CHINESE RES ACAD OF ENVIRONMENTAL SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410913249.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-09
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The prior art has problems such as corrosion, passivation and blockage of materials in removing trichloroethylene pollution in groundwater, resulting in inactivation of materials and difficulty in achieving efficient repair.

Method used

Biohydrogenated carbon-iron composite materials were prepared by hydrothermal method, and biohydrogenated carbon was used as a support, combining the reduction properties of zero-valent iron and the adsorption properties of biochar to prepare composite materials with high specific surface area and porous structure.

Benefits of technology

It has achieved efficient adsorption and reduction of trichloroethylene in groundwater, and has dual advantages. It can deeply repair groundwater containing trichloroethylene. The materials are simple to operate, low cost, and green and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119771348A_ABST
    Figure CN119771348A_ABST
Patent Text Reader

Abstract

The invention relates to a biological hydrogenated carbon-iron composite material, which is obtained by the following method: 1) carrying out hydrothermal reaction, roasting, filtering and recycling on wood chips to obtain hydrogenated charcoal with a porous structure and a high specific surface area; and 2) mixing the biological hydrogenated carbon in the step 1 with an iron salt, adding the mixture into water, performing ultrasonic treatment at room temperature, drying at 90-110 DEG C, performing heat treatment in a muffle furnace in a nitrogen atmosphere, washing with ethanol, and draining at room temperature to obtain the biological hydrogenated carbon-iron composite material. The invention also provides a preparation method of the composite material. The biological hydrogenated carbon-iron composite material prepared from the wood chips has the dual advantages of adsorption and reduction of trichloroethylene, and deep remediation of underground water containing trichloroethylene can be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of groundwater pollution restoration in the field of environmental protection, and specifically relates to a biohydrogenated carbon-iron composite material.

[0002] The invention also relates to a method for preparing the biohydrogenated carbon-iron composite material.

[0003] The present invention also relates to the application of the above-mentioned biohydrogenated carbon-iron composite material in removing trichloroethylene pollution in groundwater. Background Art

[0004] Trichloroethylene is a commonly used cleaning agent in industry. It is colorless, volatile, and difficult to dissolve in water, but soluble in organic solvents such as alcohol and ether. With its good compatibility chemical properties, it was once widely used in circuit board cleaning, metal surface decontamination and cleaning, clothing dry cleaning, as well as printing inks, adhesives, spot removers, etc. Due to its high toxicity, long-term contact or inhalation of trichloroethylene can cause harm to human health, such as damage to the liver, kidneys and nervous system. In 2012, the International Cancer Research Center (IARC) upgraded the rating of trichloroethylene to a human carcinogen. Trichloroethylene mainly enters the soil and groundwater environment through leakage and discharge during industrial production and waste treatment. Due to its strong migration ability in the soil, trichloroethylene can penetrate the tiny pores of the soil and migrate to the groundwater environment, causing groundwater pollution. It is reported that in some industrial areas and waste disposal sites, trichloroethylene content in groundwater exceeds the standard seriously. For example, groundwater pollution to varying degrees has occurred in the Beijing-Tianjin-Hebei region, the Pearl River Delta region, Tancheng City in Shandong Province, and Pudong New Area in Shanghai, posing a threat to the surrounding environment and residents' health.

[0005] At present, the commonly used remediation methods for trichloroethylene contaminated sites include chemical reduction based on zero-valent iron, advanced oxidation methods represented by Fenton reagent and sodium persulfate, and biological methods based on dehalogenating bacteria. Among them, the chemical reduction method is environmentally friendly and economical, and is currently the most widely used technology for the remediation of trichloroethylene contaminated sites. As a reducing agent, zero-valent iron is often used in in-situ permeable reaction walls, in-situ injection and other technologies. It has strong reducing ability and can achieve in-situ efficient dechlorination and degradation of trichloroethylene. Although zero-valent iron has been widely used in the degradation of trichloroethylene, it is prone to corrosion, passivation and clogging, resulting in material inactivation. Therefore, the development of a low-cost, stable-performance zero-valent iron material is an important way to solve the application prospects of groundwater trichloroethylene remediation.

[0006] Biochar-iron composite material is a material composed of biological activated carbon and zero-valent iron. It has the characteristics of high specific surface area, porous structure, rich functional groups and magnetism. It can be used for the remediation of halogenated hydrocarbon pollutants such as trichloroethylene in groundwater. Among them, biochar is a renewable carbon source with the characteristics of wide source, low cost and large specific surface area. It can be used as an important carrier for the preparation of iron-carbon materials. The hydrothermal method is a method of reacting in a heated and pressurized aqueous solution. It has the advantages of mild reaction conditions, fast reaction speed and high reaction selectivity. It can be used to prepare various micro-nano materials. The biochar and iron salt are mixed and reacted by the hydrothermal method, and then pressurized reduction can prepare an iron-carbon composite material with a porous structure and a high specific surface area. Summary of the invention

[0007] The purpose of the present invention is to provide a biohydrogenated carbon-iron composite material.

[0008] Another object of the present invention is to provide a method for preparing the above-mentioned biohydrogenated carbon-iron composite material.

[0009] To achieve the above purpose, the biohydrogenated carbon-iron composite material provided by the present invention is obtained by the following method:

[0010] 1) subjecting sawdust to hydrothermal reaction, roasting, and filtering, and recovering hydrogenated biochar having a porous structure and a high specific surface area;

[0011] 2) Mix the hydrogenated biochar and iron salt in step 1, add them to water, ultrasonically treat at room temperature, dry at 90-110° C., heat treat in a muffle furnace under a nitrogen atmosphere, wash with ethanol, and filter dry at room temperature to obtain a biohydrogenated carbon-iron composite material.

[0012] The preparation method of the above-mentioned biohydrogenated carbon-iron composite material provided by the present invention comprises the following steps:

[0013] 1) subjecting sawdust to hydrothermal reaction, roasting, and filtering to recover biohydrogenated carbon having a porous structure and a high specific surface area;

[0014] 2) Mixing the biohydrogenated carbon and iron salt in step 1, adding them to water, ultrasonically treating at room temperature, drying at 90-110° C., heat treating in a muffle furnace under a nitrogen atmosphere, washing with ethanol, and filtering and drying at room temperature to obtain a biohydrogenated carbon-iron composite material.

[0015] In the preparation method, the wood chips in step 1 are any one of agricultural waste, food processing waste, forestry waste or a mixture thereof.

[0016] In the preparation method, the heating rate of the hydrothermal reaction in step 1 is 2-20°C / min, the heating temperature is 100-300°C, and the hydrothermal reaction time is 20-45min.

[0017] In the preparation method, the mass ratio of the biohydrogenated carbon and the iron salt in step 2 is 1:1-1:5.

[0018] In the preparation method, the iron salt in step 2 is any one of ferric sulfate, ferric nitrate, ferric chloride or a mixture thereof.

[0019] In the preparation method, the ultrasonic treatment time at room temperature in step 2 is 5-60 minutes, the heat treatment temperature in the muffle furnace is 400-900° C., and the heat treatment time in the muffle furnace is 20-120 minutes.

[0020] The biohydrogenated carbon-iron composite material provided by the invention can be used to remove trichloroethylene pollution in groundwater.

[0021] The remarkable effects of the present invention are:

[0022] 1. The present invention selects biohydrogenated carbon as a carrier to prepare an iron-carbon composite material with high reducing ability and catalytic activity, which is simple to operate, low in cost, green and environmentally friendly, universal, and easy to mass produce;

[0023] 2. The biohydrogenated carbon-iron composite material prepared by the present invention has the dual advantages of adsorption and reduction of trichloroethylene, and can achieve deep remediation of groundwater containing trichloroethylene. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The present invention is a flow chart of the preparation method of the biohydrogenated carbon-iron composite material.

[0025] Figure 2 This is a diagram showing the effect of the biohydrogenated carbon-iron composite material prepared in Example 1 on removing trichloroethylene from groundwater.

[0026] Figure 3 This is the SEM morphology of the biohydrogenated carbon-iron composite material of Example 2.

[0027] Figure 4 This is the XRD characterization of the biohydrogenated carbon-iron composite material of Example 2.

[0028] Figure 5 This is a diagram showing the effect of the biohydrogenated carbon-iron composite material prepared in Example 2 on removing trichloroethylene from groundwater.

[0029] Figure 6 This is a comparison diagram of the effects of the biohydrogenated carbon-iron composite material prepared in Example 1 of the present invention and the known activated carbon-iron composite material on degrading trichloroethylene in a groundwater environment. DETAILED DESCRIPTION

[0030] The present invention provides a biohydrogenated carbon-iron composite material, a preparation method and a use thereof, specifically, hydrothermally mediating lignin to generate biohydrogenated carbon, reducing the biohydrogenated carbon to achieve zero-valent iron generation, and regulating the preparation temperature to strengthen the binding effect between the biohydrogenated carbon and the zero-valent iron. The biohydrogenated carbon-iron composite material can fully combine the reduction performance advantages of zero-valent iron and the adsorption performance advantages of biochar, and can achieve a more effective adsorption, reduction and removal effect of trichloroethylene than a single raw material.

[0031] The first step of the present invention is to generate biohydrogenated carbon from lignin by hydrothermal mediating, and the specific process is as follows:

[0032] The sawdust is added into deionized water, put into a high-pressure reactor, heated to a specified temperature at a certain heating rate, subjected to a hydrothermal reaction, and roasted for a required time, and then filtered and recovered to obtain a biohydrogenated carbon with a porous structure and a high specific surface area.

[0033] The sawdust is any one of agricultural waste, food processing waste, forestry waste, etc. or a mixture thereof, the heating rate is 2-20°C / min, the heating temperature is 100-300°C, and the duration is 20-45min.

[0034] The second step of the present invention is to reduce and prepare zero-valent iron, while strengthening the combination with biohydrogenated carbon. The specific process is as follows:

[0035] Biohydrogenated carbon and iron salt are mixed in a certain proportion, added to water, ultrasonically treated at room temperature for a certain time, dried at 105°C for 24 hours, and heat treated in a muffle furnace under a nitrogen atmosphere for a specified time to prepare a biohydrogenated carbon-iron composite material with a porous structure and a high specific surface area.

[0036] The iron salt is any one of iron sulfate, iron nitrate, iron chloride, etc. or a mixture thereof, the mass ratio of biohydrogenated carbon to iron salt is 1:1-1:5, the ultrasonic treatment time at room temperature is 5-60 minutes, the heat treatment temperature in the muffle furnace is 400-900°C, and the heat treatment time in the muffle furnace is 20-120 minutes. The collected biohydrogenated carbon-iron composite material is washed 3 times with ethanol and filtered to dry at room temperature.

[0037] The biohydrogenated carbon-iron composite material of the invention can be applied to the treatment of groundwater containing trichloroethylene.

[0038] The present invention will be further described below by way of examples and drawings.

[0039] Example 1

[0040] The organisms selected in this embodiment are corn stalks, and the iron salt is ferric sulfate. The biohydrogenated carbon-iron composite material is prepared by hydrothermal method to degrade trichloroethylene in groundwater. Figure 1As shown, the specific steps are as follows:

[0041] (1) 10 g corn straw was added to 500 mL deionized water, placed in a high-pressure reactor, heated to 200 °C at a heating rate of 5 °C / min, maintained for 20 min, and cooled to room temperature to obtain a black solid product. After filtering and washing, it was dried at 105 °C for 24 h to obtain hydrogenated biochar with a porous structure and a high specific surface area.

[0042] (2) 10 g of the biohydrogenated carbon prepared above and 20 g of ferric sulfate were mixed, added to 100 mL of water, ultrasonicated for 40 min, vacuum filtered, dried at 105 °C for 24 h, calcined at 500 °C in a muffle furnace for 40 min under nitrogen conditions, and rinsed with ethanol to obtain a biohydrogenated carbon-iron composite material.

[0043] (3) Take 5g of the biohydrogenated carbon-iron composite material and add it to a 120mL conical flask reactor, prepare 50mL of trichloroethylene solution with an initial concentration of 10mg / L, and react for 24h under light-free conditions, which can achieve 95.34% removal of trichloroethylene. The removal effect of trichloroethylene in groundwater in the biohydrogenated carbon-iron composite material in this example can be seen in Figure 2 .

[0044] Example 2

[0045] The organisms selected in this embodiment are pine wood chips, and the iron salt is ferric nitrate. The biohydrogenated carbon-iron composite material is prepared by hydrothermal method to degrade trichloroethylene in groundwater. The specific steps are as follows:

[0046] (1) 10 g of pine sawdust was added to 500 mL of deionized water, placed in a high-pressure reactor, heated to 300 °C at a heating rate of 10 °C / min, maintained for 40 min, and cooled to room temperature to obtain a black solid product. After filtering and washing, it was dried at 105 °C for 24 hours to obtain a biohydrogenated carbon with a porous structure and a high specific surface area.

[0047] (2) 10 g of the above-prepared biohydrogenated carbon and 40 g of ferric nitrate were mixed, added to 100 mL of water, ultrasonicated for 60 min, vacuum filtered, dried at 105 ° C for 24 hours, calcined in a muffle furnace at 800 ° C for 60 min under nitrogen conditions, and rinsed with ethanol to obtain a biohydrogenated carbon-iron composite material. After SEM characterization, it was found that the material had a porous structure and a high specific surface area. The SEM and XRD characterization morphology of the biohydrogenated carbon-iron composite material prepared in this example can be found in Figure 3 , Figure 4 .

[0048] (3) Take 5g of the biohydrogenated carbon-iron composite material and add it to a 120mL conical flask reactor, prepare 50mL of trichloroethylene solution with an initial concentration of 10mg / L, and react for 24h under light-free conditions, which can achieve 97.46% removal of trichloroethylene. The removal effect of trichloroethylene in groundwater in the biohydrogenated carbon-iron composite material in this example can be seen in Figure 5 .

[0049] Comparative Example 1

[0050] Different from Example 1, this comparative example adopts the known technology to prepare the activated carbon-iron composite material, and the process is:

[0051] 10g corn stalks were placed in a muffle furnace. Under nitrogen conditions, the heating rate was 3℃ / min. The heating started from room temperature until the predetermined temperature of 700℃, and stayed at this temperature for 2h. After the carbonization was completed, the air was isolated outside the furnace for natural cooling. The subsequent zero-valent iron loading process was the same as in Example 1. The 10g activated carbon prepared above and 40g ferric nitrate were mixed, added to 100mL water, ultrasonicated for 60min, vacuum filtered, dried at 105℃ for 24h, calcined at 800℃ in a muffle furnace under nitrogen conditions for 60min, and rinsed with ethanol to obtain an activated carbon-iron composite material.

[0052] The degradation effects of the activated carbon-iron composite material prepared in this comparative example and the biohydrogenated carbon-iron composite material prepared in Example 1 in the groundwater environment are compared. Figure 6 As shown. Figure 6 It shows that the efficiency of the known activated carbon-iron composite material in degrading trichloroethylene in 24 hours is 54.2%, which is very different from the effect of Example 1.

Claims

1. A biohydrogenated carbon-iron composite material obtained by the following method: 1) subjecting sawdust to hydrothermal reaction, roasting, and filtering, and recovering biohydrogenated carbon having a porous structure and a high specific surface area; 2) Mixing the biohydrogenated carbon and iron salt in step 1, adding them to water, ultrasonically treating at room temperature, drying at 90-110° C., heat treating in a muffle furnace under a nitrogen atmosphere, washing with ethanol, and filtering and drying at room temperature to obtain a biohydrogenated carbon-iron composite material.

2. The method for preparing the biohydrogenated carbon-iron composite material according to claim 1, comprising the following steps: 1) subjecting sawdust to hydrothermal reaction, roasting, and filtering, and recovering hydrogenated biochar having a porous structure and a high specific surface area; 2) Mixing the biohydrogenated carbon and iron salt in step 1, adding them to water, ultrasonically treating at room temperature, drying at 90-110° C., heat treating in a muffle furnace under a nitrogen atmosphere, washing with ethanol, and filtering and drying at room temperature to obtain a biohydrogenated carbon-iron composite material.

3. The preparation method according to claim 2, wherein The wood chips in step 1 are any one of agricultural waste, food processing waste, forestry waste or a mixture thereof.

4. The preparation method according to claim 2, wherein The heating rate of the hydrothermal reaction in step 1 is 2-20°C / min, the heating temperature is 100-300°C, and the hydrothermal reaction time is 20-45min.

5. The preparation method according to claim 2, wherein: The mass ratio of the biohydrogenated carbon and the iron salt in step 2 is 1:1-1:

5.

6. The preparation method according to claim 2, wherein: The iron salt in step 2 is any one of ferric sulfate, ferric nitrate, ferric chloride or a mixture thereof.

7. The preparation method according to claim 2, wherein: In step 2, the ultrasonic treatment time at room temperature is 5-60 minutes, the heat treatment temperature in the muffle furnace is 400-900° C., and the heat treatment time in the muffle furnace is 20-120 minutes.

8. Use of the biohydrogenated carbon-iron composite material according to claim 1 in removing trichloroethylene pollution from groundwater.

Citation Information

Patent Citations

  • Preparation method of charcoal-loaded zero-valent iron catalytic material

    CN109225221A

  • Preparation method of biochar-loaded zero-valent iron composite material

    CN109603751A